2019
DOI: 10.1101/599902
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The HAC1 Histone Acetyltransferase Promotes Leaf Senescence via Regulation of ERF022

Abstract: 1Nutrient remobilization during leaf senescence nourishes the growing plant. Understanding the 2 regulation of this process is essential for reducing our dependence on nitrogen fertilizers and increasing 3 agricultural sustainability. Our lab is interested in chromatin changes that accompany the transition to 4 leaf senescence. Previously, darker green leaves were reported for Arabidopsis thaliana hac1 mutants, 5 defective in a gene encoding a histone acetyltransferase in the CREB-binding protein family. Here,… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 48 publications
(42 reference statements)
0
3
0
Order By: Relevance
“…Because of the early flowering phenotype of the hda15 and why1hda15 mutants, we further compared the DEGs in the hda15 or why1hda15 mutants (fold change >1.5, FDR <0.05) to 389 bolting‐associated genes (BAGs) from a previously published dataset (Hinckley et al, 2019). This showed that the expression of 77 or 87 BAGs was significantly up‐regulated whereas 93 or 102 down‐regulated in hda15 or why1hda15 , respectively (Figure S8A, B).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Because of the early flowering phenotype of the hda15 and why1hda15 mutants, we further compared the DEGs in the hda15 or why1hda15 mutants (fold change >1.5, FDR <0.05) to 389 bolting‐associated genes (BAGs) from a previously published dataset (Hinckley et al, 2019). This showed that the expression of 77 or 87 BAGs was significantly up‐regulated whereas 93 or 102 down‐regulated in hda15 or why1hda15 , respectively (Figure S8A, B).…”
Section: Resultsmentioning
confidence: 99%
“…In Arabidopsis , histone acetyltransferase 1 ( hac1 ) mutants display delayed age‐related developmental senescence. Moreover, hac1 increased the levels of H3K9ac and H3K4me3 and the expression of ERF022 , which is a positive regulator of leaf senescence (Hinckley et al, 2019). Furthermore, HDA9 and HOS15 form a complex with PWR and WRKY53 to repress the expression of the negative regulators during senescence (Chen et al, 2016; Zareen et al, 2022).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation